Marketing, advertising, and branding in Fortnite: how do brands and companies connect today to audiences through the metaverse? - Sidorenko-Bautista, Pavel; Castillo Abdul, Bárbara; Herranz de la Casa, José María; Abellán Hernández, María (Cogent Social Sciences, 2025)
The rise of digital marketing has significantly impacted the audio-visual industry,particularly in the online video game sector. this study, focusing on Fortnite as a casestudy, explores the connections between brands’ strategic practices and immersivegaming in the metaverse. the research adopts a qualitative methodological approachto analyze the typology of advertising and marketing efforts undertaken by brands andcompanies through disruptive digital platforms in the metaverse. Beyond being asimple digital entertainment, Fortnite has become a key space for socialization andexperimentation for young and emerging audiences. the concept of ‘transmedia’ isrevisited considering the revitalization that new technologies bring to the field,highlighting the importance of emotional and social bonds that consumers of this typeof content practice. the study emphasizes the role of user participation and theparticipatory logic required by transmedia strategies as a formula to explore theinteractions between brands and users in the metaverse. the fragmentary nature ofmetaverses, derived from the multiplicity of interfaces and environments, is alsodiscussed. the research underscores the importance of user engagement in thenarrative, as users frequently become creators and disseminators of content both withinand outside the metaverse, forming a community and providing feedback on the spaceand narrative in which they interact with other users.
Keywords: fortnite; metaverse; videogame; marketing; social media; sponsorship